Transition to Long-Term Baccalaureate School in Switzerland: Governance, Tensions, and Justifications - Sandra Hafner; Raffaella Simona Esposito; Regula Julia Leemann (MDPI AG, 2022)
In Switzerland, the baccalaureate school is an important pathway to university education, and the aspirations of families and students to enter baccalaureate school have grown. However, vocational education and training (VET) remains the predominant educational pathway and has a strong lobby. We investigate how in this context, the transition from primary education to baccalaureate school is governed and justified at the cantonal level. We study how two Swiss cantons try to meet the official or unofficial maximum baccalaureate quotas desired by educational policymakers through different selection procedures and admission criteria. Drawing on the Economics of Conventions, we conceptualize selection procedures as cantonal transition chains and show that the strategies, procedures, and instruments applied in governance are rooted in diverse principles of action. This causes tensions within cantons. Our analysis shows that agency and regulating effects in the governance of transitions must be understood as distributed among actors, technologies, and objects.